Pore Characterization and Mechanical Properties of Triply Periodic Minimal Surfaces Porous Structures by Fused Deposition Modelling - Heng Liang, Fan; Abdullah Yassin,; Khairul Fikri Tamrin,; Sinin Hamdan, (International Journal of Integrated Engineering, 2025)
This paper focuses on the design and characterization of porous structures inspired by Triply Periodic Minimal Surfaces (TPMS) in the context of additive manufacturing. Uniform porous structures with porosities of 40% (P40), 50% (P50), and 60% (P60) are designed, along with a gradient porous structure with an average porosity of 50% (ZP50). Fused Deposition Modelling (FDM) serves as the fabrication method for these TPMS-based structures. The printing accuracy, mechanical properties and energy absorption characteristics of the TPMS porous structures with different porosity are investigated. A comprehensive evaluation reveals that the actual porosity deviates from the designed values by less than 4%, affirming the reliability of the design approach. Notably, an increase in porosity correlates with an increase in ultimate yield strength, reaching a peak value of 8.644 MPa for P40. Additionally, ZP50 shows a 15.54% higher yield strength than P50 under similar porosity conditions. This advantage persists up to a strain level of 26%, where ZP50 also outperforms P50 in energy absorption characteristics. The findings enrich the understanding of the mechanical behaviour of small-scale curved porous structures created through additive manufacturing. The research offers valuable insights for engineering applications that require optimized porous structures, thereby contributing to advancements in the additive manufacturing field.